Shared Genes and Pathways in Ulcerative Colitis and Ankylosing Spondylitis: Functional Validation and Implications for Diagnosis - Li L; An G; Li F; Zhang D; Zhu X; Liang C; Zhao Y; Xie K; Zhou P; Zhu H; Jin X; Du L (Journal of Inflammation Research)
Lin Li,* Guangqi An,* Fuzhen Li,* Donghui Zhang, Xinyue Zhu, Chunyu Liang, Yu Zhao, Kunpeng Xie, Pengyi Zhou, Haiyan Zhu, Xuemin Jin,* Liping Du* Department of Ophthalmology, The First Affiliated Hospital of Zhengzhou University, Henan Province Eye Hospital, Henan International Joint Research Laboratory for Ocular Immunology and Retinal Injury Repair, Zhengzhou, Henan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuemin Jin; Liping Du, Department of Ophthalmology, The First Affiliated Hospital of Zhengzhou University, No. 1 Jianshe East Road, Zhengzhou, 450000, People’s Republic of China, Tel +8613603983193 ; +8613838191481, Email jinxuemin@zzu.edu.cn; dulplab@live.cnBackground: Associations between ulcerative colitis (UC) and ankylosing spondylitis (AS) have been reported in multiple studies, but the common etiologies of UC and AS remain unknown. Thus, in the current study, we aimed to investigate the shared genes and relevant mechanisms in UC and AS.Methods: Using datasets for UC (GSE113079) and AS (GSE1797879), we initially identified differentially expressed genes (DEGs) through differential expression analysis. The DEGs from both datasets were intersected to identify common DEGs, relevant to both UC and AS, which were used in receiver operating characteristic (ROC) curve analysis to confirm key genes in the shared pathway. Gene set enrichment analysis (GSEA) was used to obtain information on key gene pathways and interactions with UC or AS-related diseases, followed by immune infiltration analysis. Finally, peripheral blood samples of AS and UC were used to verify the mRNA expression of the eight key genes using reverse transcription-polymerase chain reaction (RT-PCR).Results: Our results revealed that GMFG, GNG11, CLEC4D, CMTM2, VAMP5, S100A8, S100A12 and DGKQ are potential diagnostic biomarkers of AS and UC. Rimegepant, eptinezumab, methotrexate, atogepant, and ubrogepant were identified as potential drugs for S100A12 and S100A8 in patients with UC and AS. GSEA showed that these key genes were associated with antigen processing and presentation, natural killer cell mediated cytotoxicity and the T cell receptor signaling pathway in AS and UC, and were significantly associated with immune cells in various immune-related pathways. Subsequent functional experiments revealed significant increases in the mRNA expressions of S100A12 and VAMP5 in patients with AS and UC. Additionally, CLEC4D mRNA expression was notably higher in patients with UC than in healthy controls.Conclusion: Key genes and shared pathways were identified in UC and AS, which may improve understanding of their relationship and guide diagnosis and treatment strategies.Keywords: ulcerative colitis, ankylosing spondylitis, diagnosis, etiology